REBRANDING DENGAN PEMBUATAN FEED DAN LOGO PADA AKUN INSTAGRAM HANY COLLECTION GUNA MENINGKATKAN JUMLAH KONSUMEN - Nabillah Amira Firdausi; Poppy Febriana; Ainur Rochmaniah (Universitas Mataram, 2024)
Online marketing is a marketing process where transactions are carried out online through electronic media such as cellphones, tablets or laptops. Online marketing can be done with various applications, one of which is the Instagram application which is a social media application included in digital media. Instagram can be used for many things, in addition to posting photos Instagram can also be used as a free promotional media that can brand products to be better known by the public. But even though Instagram can be a promotional media. There are still many people who do not know how to use Instagram optimally, especially home industry owners who are still unfamiliar with online things. Therefore, a mentoring activity is needed to explain and also guide home industry players to be able to use online marketing using Instagram. The purpose of this activity is to help hany collection to rebrand Instagram social media accounts so that products are better known by consumers. By holding this mentoring activity, it is hoped that home industry players can be more effective and also creative in running a business to expand the market and can make good use of existing technology. The results of this activity produce positive values where through the activities carried out participants can use Instagram social media to promote and post products that are sold. And also can make Instagram feeds, product photos and logos more attractive. That way the quality of the home industry in Banjar Panji village can improve better and is expected to have good progress from day to day.